A Study of the Prospects and Opportunities for India's Development in a Competitive Environment between the US and China: Based on International Trade - Li, Mohao (International Journal of Global Economics and Management, 2024)
The contemporary international environment is characterised by a particularly high-profile rivalry between China and the United States, which has expanded from the economic, technological and military spheres to the global strategic level. At the heart of this rivalry lies the global influence of both countries and their visions for the international order. The United States, as a long-time global hegemon, is facing a China with a growing economy, breakthroughs in science and technology innovation, and a significantly stronger military. The U.S. will increasingly feel the risk of being overtaken and replaced by China, and will inevitably take containment measures against China while it still has the upper hand. But at the same time in its competitive environment also for the development of India's trade brings a certain wind and opportunity, such as bringing investment or trade opportunities. Overall, the general environment of Sino-US competition is complex and volatile, and the interaction between the two countries not only affects the two countries themselves, but also has a far-reaching impact on the stability and development of the global economy and trade. Against this backdrop, India needs to pay close attention to the dynamics of the US-China relationship and the competitive dynamics between the two countries in various fields around the globe, while at the same time strengthening its own strengths and enhancing its competitiveness in order to cope with the opportunities and challenges it presents.